THE OPPRESSION TOWARD KINO IN JOHN STEINBECK’S THE PEARL - Debora Levy Savellina (Universitas Katolik Widya Mandala Surabaya, 2018)
This research discusses the oppression that happens in Kino’s life and the effect of its oppression. It focusees on two major purposes: (1) to find out and describe the oppression seen through in John Steinbeck’s The Pearl. (2) to know the effects toward Kino in John Steinbeck’s The Pearl. This research uses written data. The data and the theories are taken from written form and internet browsing. In this study, the researcher uses some theories. They are character, characterization, oppression and ethnicity and race. Furthermore, the approaches which are used are sociological approach and psychological approach. The approaches are applied to determine the approach in analyzing the oppression and the effect in The Pearl. Library research is applied for the method data collection. The result of the research shows that there are two main oppressions in The Pearl. The first oppression comes from the doctor and the second oppression comes from the pearl buyers. The doctor does not want to treat Kino. It makes Kino frustrated and disappointed with himself. Kino thinks that everything happens in his life is because of his fault. The pearl buyers try to cheat on Kino. They lie to Kino about the pearl to get a lot of money. They think they can buy Kino’s pearl with a low price and sell it with high price. Kino gets angry to people around him and himself. Kino feels disappointed, angry and hate everything in his life. In the end of the story, Kino tries to struggle with any problems which come to his life and always believes that he can overcome it.